Kelas Demokratis dan Sekolah Inklusif dalam Pengembangan Motivasi Belajar dan Kreativitas Pemecahan Masalah Keagamaan - Darmawan, Didit; El Barkah, Achmad Afad (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine students’ perceptions of freedom of expression in democratic classrooms and its impact on motivation and creativity in solving religious problems, whilst also exploring the role of an inclusive school environment in optimising learning outcomes. The method employed is a qualitative literature review with thematic analysis of relevant research findings. The findings indicate that students perceive freedom of expression as a safe space to express opinions, ask questions, and engage in discussion without pressure, thereby enhancing intrinsic motivation and engagement in learning. These conditions foster the development of students’ creativity in responding to religious issues in a reflective and innovative manner. Furthermore, an inclusive school environment plays a crucial role in accommodating the diversity of students’ creative potential through the appreciation of differences, the provision of spaces for developing interests, a diverse assessment system, and a collaborative social climate. In this context, students can achieve optimal learning outcomes in line with their individual capacities. These findings underscore the importance of the teacher’s role in facilitating open dialogue, as well as the need for school policies that systematically support inclusivity. Further research is recommended using an empirical approach to explore students’ subjective experiences in greater depth.